#1**+2 **

x^2 + 36 = 0

x^2 = -36 take both roots

x = ±√[-36]

x = ±√[-1* 36]

x = ±i√36

x = ± 6i

CPhill Jul 2, 2019

#2**+9 **

( x + 6i ) ( x - 6i ) = 0

\(x = \pm\ 6i\)

-\(tommarvoloriddle\)

Edit: For anyone who cares enough to look at my post and wants to know how to do the plus-minus sign in latex, it is \pm . On websites like AoPS, it is $\pm$ .

tommarvoloriddle
Jul 2, 2019

#3**+2 **

Whenever you have an equation in this form, try to isolate x, then take the square roots of both sides

This is called the square roots method.

CalculatorUser
Jul 2, 2019

#4**+9 **

Yeah by still it's a different way... I personally like CPhills way, but I like presenting 2 sides, which is why I posted on CPhills answer.

-\(tommarvoloriddle\)

tommarvoloriddle
Jul 3, 2019